2018
DOI: 10.3390/ma11112306
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Statistics for Inorganically-Bound Core Materials

Abstract: In this article, we study the fracture characteristics of inorganically-bound foundry cores. It will be shown that the fracture stress of inorganic cores follows Weibull’s strength distribution function for brittle materials. Using three-point and four-point-bending experiments, the volume dependence of the bending fracture stress is analyzed and a Weibull model fitted. Furthermore, the fracture stress of arbitrary bending experiments can be calculated based on the Weibull parameters found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Please note that in this section all experimental results are scaled to the effective volume of the three-point-bending experiment according to Weibullian statistics and the approach proposed by Lechner et al in an earlier article [ 31 ]. Furthermore, we only determined data points on one side of the hydrostatic axis in Figure 2 , due to the axial symmetry of the Drucker-Prager and the Mohr-Coulomb criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Please note that in this section all experimental results are scaled to the effective volume of the three-point-bending experiment according to Weibullian statistics and the approach proposed by Lechner et al in an earlier article [ 31 ]. Furthermore, we only determined data points on one side of the hydrostatic axis in Figure 2 , due to the axial symmetry of the Drucker-Prager and the Mohr-Coulomb criteria.…”
Section: Resultsmentioning
confidence: 99%
“…With the experimental results in this article and previous literature [ 31 ], which show that IOB cores follow Weibull statistics and a Mohr-Coulomb failure criterion, we have to answer the question of how both findings can be merged to one consistent mechanical model.…”
Section: Mohr-coulomb Failure Criterion Based On Weakest-link Theomentioning
confidence: 93%
See 2 more Smart Citations
“…The first step of building such a mechanical simulation is to determine the basic material parameters, in order to build a material model. Lechner et al showed that inorganically-bound core materials behave like a brittle material [5]. For a brittle material, the basic material parameters for a simulation are Young's modulus, shear modulus, fracture stress and fracture strain.…”
Section: Introductionmentioning
confidence: 99%